CT-based analysis of pericoronary adipose tissue density: Relation to cardiovascular risk factors and epicardial adipose tissue volume - Hell, Michaela M.; Achenbach, Stephan; Schuhbaeck, Annika; Klinghammer, Lutz; May, Matthias; Marwan, Mohamed (Journal of Cardiovascular Computed Tomography, 2016)
Pericoronary adipose tissue (PCAT) can promote atherosclerosis. Metabolically active and inactive PCAT may display different CT densities. However, CT density could be influenced by partial volume effects and image interpolation.To investigate whether PCAT density values in CT displays differences that are larger than those attributable to interpolation and partial volume effects, which would manifest themselves through the relationship between PCAT density and distance from the contrast-enhanced coronary lumen.PCAT density analysis was performed (417 non-atherosclerotic segments, 63 patients) using dual-source CT with a threshold-based measurement method. Changes in PCAT density values depending on distance from the contrast-enhanced coronary lumen and the influence of cardiovascular risk profile were analyzed.Mean PCAT density was -78.1 ± 5.6 HU. PCAT density decreased from proximal to distal segments in the LAD (-78.0 ± 7.3 vs. -82.4 ± 7.7 HU; p < 0.001). PCAT density was higher close to the lumen compared to more peripheral locations (-76.0 ± 6.7 vs. -78.5 ± 5.4 HU; p < 0.001). Decreasing PCAT density was significantly associated with higher epicardial adipose tissue (EAT) volume and body mass index. There was a trend of lower PCAT values with a family history of coronary artery disease.CT-measured attenuation of PCAT is influenced by EAT volume and body mass index. A decrease of PCAT attenuation with increasing distance from the vessel and from proximal to distal segments may suggest variations in CT density of PCAT due to partial volume effects and image interpolation rather than solely due to differences in tissue composition or metabolic activity.
EVALuna2:12033